Correlation between human health and reactive oxygen species produced in blood: a long-term chemiluminescence and fluorescence analysis - Kimiko Kazumura (Nature Portfolio, 2021)
Abstract The previous slide-glass type system could simultaneously detect reactive and highly reactive oxygen species, i.e., superoxide radicals (O2 −·) and hypochlorite ions (OCl−) elicited from leucocytes in sample blood, but had some drawbacks, i.e., signal noise from air-flow stirring, potential biohazard risks, etc. because of open samples placed on a slide glass. We overcame these drawbacks by adopting a fluidic-chip container in a new system, which resulted in higher sensitivity and more stable measurements. Using the new system, we conducted a pilot study on nominally healthy volunteers to find whether or not the monitored activities of leukocytes can distinguish more or less unhealthy conditions from healthy ones. At first, healthy volunteers of both genders and of various ages showed that the fluctuation magnitudes (%) of O2 −· and OCl− were nearly similar to each other and to that of the neutrophil count fluctuation. These parameters sometimes exceeded the healthy fluctuation range. By comparing these large fluctuations with the data of an inflammation marker C-reactive protein (CRP), the neutrophil count fluctuation and the timings/symptoms of abnormalities found in questionnaire, we could gain information suggesting the factors causing the large fluctuations. The new system could detect bodily abnormalities earlier than CRP or self-aware symptoms.